The Effect of Teams Games Tournament Learning Model Assisted by Snakes and Ladders Game on Learning Outcomes in Human Circulatory System Material at SMA Negeri 1 Delitua - Evi Bunga Kirani; Herkules (UNIVERSITAS PGRI MADIUN, 2026)
This study aims to determine the effect of the Teams Games Tournament (TGT) cooperative learning model assisted by the Snakes and Ladders game on students' learning outcomes regarding the human circulatory system at SMA Negeri 1 Delitua. The research employed a quasi-experimental method using a Non-equivalent Control Group Design involving 71 eleventh-grade students divided into an experimental group (TGT with Snakes and Ladders) and a control group (direct instruction). Learning outcomes were measured using pre-test and post-test instruments and analyzed through ANCOVA. The results showed that the TGT model assisted by the Snakes and Ladders game had a statistically significant positive effect on students’ learning outcomes compared to direct instruction, with higher post-test scores and a large effect size (η² = 0.146). The experimental group also demonstrated greater learning gains and a more uniform distribution of student performance, indicating that lower-performing students benefited from the collaborative and game-based activities. In conclusion, integrating traditional game-based media into the TGT learning model is an effective and innovative strategy for improving biology learning outcomes, particularly in complex topics such as the human circulatory system.